Practical intership report : L'oreal brandstorm (2009)
This project begins as part of a global contest, called Brandstorm L ́Oreal 2008; proposed by L ́Oreal in order to find new ideas and marketing strategies geared towards young people, for a new line of sun care products. L ́Oreal is looking for an appropriate way to reach both genres between the ages of 13 and 25, adjusting the new products to the needs, desires, and habits of that target group